Non cystic fibrosis bronchiectasis - (:unkn) unknown (My University, 2000)
Bronchiectasis is becoming less common as the treatment for acute lower respiratory tract infections improves and immunization programmes decrease the frequency of pertussis and measles. However bronchiectasis is still a challenge to the paediatric chest physicians in many developing parts of the world and it remains a frequent problem being the final common pathway of several different lower respiratory tract insults such as cystic fibrosis, immunodeficiency, ciliary dyskinesia. Although the treatment of patients with bronchiectasis is primarily medical, surgical treatment is required in a small group of patients with recurrent episodes of pneumonia and atelectasis localized to one area, severe or recurrent hemoptysis and in those unresponsive to aggressive medical treatment with abnormal growth and development. There are unanswered questions about childhood bronchiectasis, mainly on aetiology and treatment which require more research.
Keywords: Humans; Child; Bronchiectasis